Gene expression profiling of protease and non-protease genes in Trichophyton mentagrophytes isolates from dermatophytosis patients by qRT-PCR analysis - Shyama Datt (Nature Portfolio, 2021)
Abstract Trichophyton mentagrophytes secretes Metallocarboxypeptidase A and B of the M14 family as endoproteases and exoprotease. T. mentagrophytes produce Metalloprotease 3 and 4 which degrades the protein into the short peptides and amino acids. To understand the host fungal relationship and identification of such genes expressed during infection is utmost important. T. mentagrophytes encodes some proteins which are associated with the glyoxylate cycle. The glyoxylate cycle enzymes have been involving in virulence of dermatophytes and their up-regulation during dermatophytes growth on keratin. On comparing the expression level of virulence protease and non-protease genes, we observed, among exoprotease protease genes, Metallocarboxypeptidase B was strongly up regulated (134.6 fold high) followed by Metallocarboxypeptidase A (115.6 fold high) and Di-peptidyl-peptidases V (10.1 fold high), in dermatophytic patients as compared to ATCC strain. Furthermore, among endoprotease, Metalloprotease 4 was strongly up regulated (131.6 fold high) followed by Metalloprotease 3 (16.7 fold high), in clinical strains as compared to T. mentagrophytes ATCC strain. While among non-protease genes, Citrate Synthase was highly expressed (118 fold high), followed by Isocitrate Lyase (101.6 fold high) and Malate Synthase (52.9 fold high). All the studied virulence genes were considered the best suitable ones by geNorm, Best keeper, Norm Finder and Ref finder.